2010
DOI: 10.1257/aer.100.1.98
|View full text |Cite
|
Sign up to set email alerts
|

“Momma's Got the Pill”: How Anthony Comstock and Griswold v. Connecticut Shaped US Childbearing

Abstract: The 1960s ushered in a new era in US demographic history characterized by significantly lower fertility rates and smaller family sizes. What catalyzed these changes remains a matter of considerable debate. This paper exploits idiosyncratic variation in the language of “Comstock” statutes, enacted in the late 1800s, to quantify the role of the birth control pill in this transition. Almost 50 years after the contraceptive pill appeared on the US market, this analysis provides new evidence that it accelerated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…Thus, potential controllers should have encountered much less resistance in the form of negative attitudes and prejudice. Nonetheless, especially in economic research, scholars have strongly emphasized that the spread of the contraceptive pill made fertility control much more efficient, and thus had far-reaching effects on women's education and career choices (Bailey 2010;Goldin and Katz 2002). It may therefore be expected that highly educated women who were married to professional men would have had lower fertility, especially in the 1970 census.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, potential controllers should have encountered much less resistance in the form of negative attitudes and prejudice. Nonetheless, especially in economic research, scholars have strongly emphasized that the spread of the contraceptive pill made fertility control much more efficient, and thus had far-reaching effects on women's education and career choices (Bailey 2010;Goldin and Katz 2002). It may therefore be expected that highly educated women who were married to professional men would have had lower fertility, especially in the 1970 census.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in the US in the late 1950's, social scientists have tried to disentangle the impact of access to oral contraceptives from the economic and social changes taking place at that time (Bailey, 2010). For example, economists have argued that evidence shows a significant fertility decline even before the introduction of oral contraceptives, corresponding to fundamental changes in the demand for children that are closely related to women's increasing access to the labor market (Becker, 1981).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The introduction of the contraceptive pill was one of the most significant technological innovations in the twentieth century as it provided a practical and reliable tool to avoid unintended pregnancies, giving women and families greater control over the timing of the pregnancies and the number of children they would bear (Bailey, 2006(Bailey, , 2010). An extensive literature has shown that having more control over fertility decisions allowed women and families to alter their life choices more freely.…”
Section: Introductionmentioning
confidence: 99%
“…Although the positive association of the fertility transition with the rise in education and its impact on the takeoff to modern growth is well established in the literature (for example, Galor, ; Dalgaard and Strulik, ), the role of contraceptives for these developments is perhaps less intensively researched. With respect to oral contraceptives, Bailey (, ) uses legal differences across U.S. states (the Comstock laws) and health policy differences across U.S. counties and show that increased contraception in the 1960s and '70s had not only a causal impact on fertility but also a positive impact on education and income of subsequent generations. In earlier times, legal as well as cultural constraints may have slowed down the uptake of modern contraceptives, but they were not able to choke off the general trend.…”
Section: Introductionmentioning
confidence: 99%